Iraq's Unwanted People - Secker, Bradley (United Kingdom, 2011)
Since the 2003 U.S. invasion of Iraq, the situation for LGBT Iraqis has worsened leading many to flee the country. “Iraq’s Unwanted People” tells the story of gay Iraqi men seeking refuge in Damascus, Syria despite homosexuality being illegal there.
Verzio Film Festival Submission
Duration: 00:07:00
Verzio Film Festival Submission
Keywords: Documentary films